Aplikasi Belajar Interaktif Algoritma Sorting Berbasis Desktop - Abdul Aziz Jabar; Andi Sofyan Anas (Puslitbang Sekawan Institute Nusa Tenggara, 2019)
Making software requires a lot of algorithms that are implemented into the making, one of the algorithms used is the sorting algorithm. Algorithms are logical sequences of steps to solve problems that are arranged systematically. Sorting algorithms (sequencing) are generally defined as the process of rearranging a series of objects in a certain order. The purpose of the sequencing process is to facilitate the search process for a beginner who wants to learn to make software, of course they have to go through stages in learning algorithms and in the learning process there will usually be obstacles faced such as not fully understanding how the algorithm works, especially the sorting algorithm or the media used as learning materials have not been able to maximize the knowledge of sorting algorithms, therefore it requires an application of learning aids media that can help in learning and understanding the material of the sorting algorithm more optimally. In making assistive media applications learn how to work the steps of the sorting algorithm, the author uses the luther-sutopo method. The stages are concept, design, collecting materials, assembly, testing, and distribution. In the application there is general material about sorting and video algorithms that can help maximize understanding of the sorting algorithm material. The results achieved by an auxiliary media application are learning desktopbased sorting algorithms that are used for learning specific sorting algorithms in theory